Benefits of hybridisation of diesel driven rail vehicles: Energy management strategies and life-cycle costs appraisal. (1st November 2015) - Meinert, M.; Melzer, M.; Kamburow, C.; Palacin, R.; Leska, M.; Aschemann, H.
Highlights: We applied different energy management strategy for optimization of fuel consumption and/or emissions. An elaboration of life cycle cost based on invest, maintenance and fuel cost were done. We considered 3 different diesel-driven system architectures. The reduction potential for fuel consumption was figures out by 20%, up to 25% applying energy management strategy. Abstract: Hybridisation of diesel-driven rail vehicles is already possible and promises significant reductions in fuel consumption and exhaust emissions (nitrogen oxides and particulate matter). However, current performance can be significantly improved by introducing technologies such as energy storage systems. The aim of this paper is to investigate the energy management strategies and technical life cycle cost aspects of railway-specific hybridisation architectures. To do so, twelve promising combinations of system architectures, energy storage systems and railway duty cycles have been selected, described and analyzed. A method based on a MATLAB/SIMULINK model has been used with three different approaches for the energy management strategy optimization (i) the Covariance Matrix Adaptation Evolution Strategy as baseline optimization; (ii) dynamic programming to determine the global optimum and (iii) a sensitivity analysis approach for the energy storage systems. Based on these boundary conditions, a hybridisation life cycle cost analysis has been carried out. As part of this analysis three different fuel price scenarios have been considered (i) low price of 0.78 €/l; (ii) medium price of 1.12 €/l; (iii) high price of 1.64 €/l. The results show that different energy storage technologies achieve diverse life cycle costs, triggering a range of investment, replacement and maintenance costs, as well as significantly reduced operational costs due to lower fuel consumption. In addition, the simulation results show that fuel consumption can be reduced up to 20%, in some cases rising to approximately 25% if energy management strategies are applied. Of these, Start/Stop and downsizing of the internal combustion engine are the most promising strategies for the emission reduction. Both require auxiliaries' electrification and appropriate integration of energy storage systems. LCC results also indicate that operational conditions with high annual mileage are most beneficial when a hybrid consisting of an internal combustion engine and an energy storage system is used in a high fuel price scenario.